Juridic Analysis of Waste Management Supervision System in Labuhanbatu District - Meso Wanolo; Bernat Panjaitan; Sriono Sriono (Budapest International Research and Critics University, 2021)
Waste management is a systematic, comprehensive, and sustainable activity that includes waste reduction and handling. Waste management is a problem that must be faced by the local government of Labuhanbatu Regency. The increasing population will affect the pattern of use of product materials and public consumption, it will indirectly affect the type and amount of waste produced. So that there is a need for supervision and law enforcement actions, both the application of administrative sanctions and criminal sanctions, then the problem of waste management will never be resolved. This study aims to determine the waste management monitoring system in Labuhanbatu Regency and to find out about the obstacles faced in the supervision of waste management in Labuhanbatu Regency. In this study, the authors used empirical juridical methods, as well as conducting field research and conducting interviews to obtain data to support the author's research. The results of the study show that the waste management and supervision system in Labuhanbatu Regency is regulated through the Labuhanbatu Regency Regional Regulation Number 8 of 2017 concerning Waste Management with a management system that is still carried out by collecting, transporting, and disposing of. Meanwhile, it should be done by sorting, collecting, transporting, managing, and finalizing waste. Meanwhile, the monitoring system carried out is still limited to monitoring which is considered not running yet and is still not optimal.